2013
DOI: 10.1108/08858621311285714
|View full text |Cite
|
Sign up to set email alerts
|

Salesperson's listening ability as an antecedent to relationship selling

Abstract: Purpose – In this study, active empathetic listening is purposed as being an antecedent to a salesperson's communication skill, ability to maintain quality relationships and build trust. The study proposes that communication skill, relationship quality and trust all moderate the relationship between AEL and sales performance. Design/methodology/approach – Survey research using salespersons was conducted; structural equation modeling was used to test the hypotheses of the model. Findings – The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 34 publications
0
43
0
2
Order By: Relevance
“…Smart technologies support salesperson' tasks execution, by changing their routines and moving some tasks from the real employees to the technology 26,27,28 . In fact, while they can use these tools for achieving knowledge of products and services that consumers want to consult, clients can self-check out without the assistance of a real seller.…”
Section: (V) Challenges Resulting From Changes In Salespersons' Jobsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart technologies support salesperson' tasks execution, by changing their routines and moving some tasks from the real employees to the technology 26,27,28 . In fact, while they can use these tools for achieving knowledge of products and services that consumers want to consult, clients can self-check out without the assistance of a real seller.…”
Section: (V) Challenges Resulting From Changes In Salespersons' Jobsmentioning
confidence: 99%
“…For instance, they provide updated information of available products, which employees may use for replying to consumers' requests, and change their routines because the usage of these systems is integrated in their activities. For instance, they may be responsible for the right functioning of a certain technology and supervise its effective usage 26,27,28 . Moreover, they are also a tool for interaction between consumers and retailers, for understanding critical issues and potential problems.…”
Section: Selling Activitiesmentioning
confidence: 99%
“…al., 1997. A Good listening skills on behalf of the seller improve trust, relationship quality and the overall communication skills of salespersons (Ramsey and Sohi, 1997;Drollinger and Lucette, 2013). Equipped with an effective interpersonal listening ability, the sales representative acquires perceptions required for an adaptive selling behaviors, which is favorable for sales performance (Spiro and Weitz, 1990;Weitz et al, 1986).…”
Section: Communication and Listening Skillsmentioning
confidence: 99%
“…Greenberg and Greenberg, (1983) had earlier suggested that, in order to be successful, a salesperson need three basic traits such as empathy, ego drive, and ego strength. Drollinger, T and Comer, L.B., (2013), predicted that Active Empathetic Listening (AEL) also had a strong relationship to trust and Trustworthiness of the salesperson would result in a better relationship between the buyer and seller. Abed, G.M.…”
mentioning
confidence: 99%